Brush Use in Lot-Fed Cattle Shows Continued Use and Positive Behaviour - Emma J. Dunston-Clarke; Catherine Stockman; Josie Sinclair; Teresa Collins (Animals)
Feedlot cattle were assessed for the consistency of enrichment brush use, higher incidence of natural behaviour, and less agonistic or abnormal behaviour compared to cattle without the brush. Cattle were assigned to one of two treatment pens, (1) access to a vertical grooming brush (EB; n = 89) or (2) no access control (CON; n = 80), for a period of 107 days. A Principal Component (PC) analysis was used on pen-side demeanour scores. Statistical analysis on pen-side behaviour and demeanour PCs tested for impact of treatment, day, and time. Frequency of brush use and the duration of each cow–brush interaction did not decrease over the assessment period. Self-grooming and allogrooming did not differ between treatments and were similar in frequency to brush grooming, resulting in total grooming being higher in the EB treatment group (p < 0.05). Cattle in the EB pen were scored as more content (PC 2; p < 0.05) and sociable (PC 3; p < 0.01), while CON cattle were scored as more anxious (PC 3; p < 0.05). Overall, this study suggests that the provision of a brush for enrichment enhanced lot-fed cattle wellbeing and permitted prolonged engagement, making it an effective enrichment device.